Michel Foucault : drôle de genre pour une psychanalyse ? - Laurie Laufer (Genre, Sexualité et Société)
Why should one read Foucault when one practices psychoanalysis? Is Foucault still a “hot topic” for psychoanalysts in 2019? For psychoanalysis not to become a dead language, reading and rereading Michel Foucault proves indeed quite relevant: it implies reading, together with him, Queer, Gay, Lesbian and Gender Studies. This article relies on queer authors such as Gayle Rubin, Eve Kosofsky-Sedgwick, and Judith Butlers, but also on Freud, Lacan and Allouch, to reflect on how we can possibly think the sexual, sexuality and gender identity in the Freudian field and beyond a hetero-normative gender binary perspective. With and after Foucault, the genealogist of Freudian psychoanalysis, what kind of a psychoanalysis would be one devoid of discourses on straight family, Oedipus, sexuality, sexual aetiology, and infantile sexuality? If reading Foucault sets forth a new erotology, it then helps find back “the political honour of psychoanalysis”.